Buying influence? The international diplomacy behind donor financing of the World Bank’s International Development Association - Xu, J (2015)
This thesis addresses the puzzle of why changes in relative donor contributions to the World Bank’s International Development Association (IDA) did not reflect shifts in their relative economic capabilities. It addresses the grand debates about how power transitions shape a US-led hegemonic international system by exploring one specific international organisation. Drawing primarily on archives, elite interviews, and participant observation, I examine sixteen rounds of IDA replenishment negotiations from 1960 to 2010. There are three puzzles a close empirical analysis throws up. The first is why the hegemon maintained its burden shares regardless of rise or fall in economic status; I call this ‘Hegemonic Lag’. The second is why ascending powers were slow to assume greater burden-shares despite economic ascents; I call this ‘Challenger Inertia.’ The third puzzle is why significant burden-shifting occurred on a much greater scale than shifts in relative economic weight; I call this ‘Accelerated Burden-Shifting.’ Two conventional explanations – donors’ relative ‘ability-to-pay’ and their ‘country-specific interests’ – offer a first-cut analysis of donors’ ability and willingness to contribute. However, they fail to uncover how bipolar geopolitics and World Bank governance shaped IDA burden-sharing dynamics. This thesis tests whether the hegemon will maintain its shares even if its relative economic capacity wanes, if its bipolar rival poses a more intense external threat. Equally it tests whether a hegemon and/or waning powers with a desire to expand total IDA resources will cede voting rights to ascending powers in exchange for financial support to IDA. Finally, the research examines whether a hegemon violating the ‘fairness’ principle by shirking obligations but pursuing undue influence will face secondary states willing to take ‘exit/voice’ measures to restore an implicit contribution-to-influence equity line; and whether such countermeasures would be postponed if secondary states are structurally dependent upon the hegemon and/or lack viable outside options. In-depth case studies are used to test these hypotheses. Overall the thesis reveals that the US maintained or cut its burden share as the Soviet threat waxed and waned; and that as the Soviet Union collapsed the US abandoned both its leadership for IDA expansion to counter the Soviet threat and its self-restraint in controlling the World Bank, provoking the fairness concern among secondary states – the most potent factor in explaining IDA burden-sharing dynamics in the post-Cold War era.